Design WAP-Based to Web-Based Patient Emergency Service System for Pusat Kesihatan Universiti (PKU) - Alatresh, Salem Asseed (2008)
With Design WAP-based to Web-based Patient Emergency Service System for Pusat Kesihatan Universiti (PKU) by using the wireless technology can be obtained easily way and flexibility to access the information at any time in any location. This research introduces a Web-WAP application that provides the Doctors of Pusat Kesihatan Universiti (PKU) by provide them with the patient information accessing anytime and anywhere to check the patient status, that save the time to check the patient status from different places. By using this technology, Doctors can easily get necessary information about their patient.